2018
DOI: 10.5433/1679-0359.2018v39n6p2761
|View full text |Cite
|
Sign up to set email alerts
|

Componentes não integrantes da carcaça de novilhos terminados em confinamento recebendo ureia protegida ou agrícola em substituição ao farelo de soja

Abstract: The effect of termination of steers in a feedlot using the total substitution of soybean meal by slow-release or agriculture urea on the non-carcass components was evaluated. Twenty-seven purebred and Charolais × Nellore castrated crossbred steers (mean age 20 months, mean initial weight 293 kg) were allocated to received concentrates containing slow degradation urea, soybean meal, or agricultural urea. The experimental design was in randomized blocks (breed predominance), with three treatments and nine replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In concordance with our study, Bourg et al [13] did not observe differences in the meat chemical composition when comparing conventional urea with SRU in finishing steers. Cardoso et al [64] reported a reduction in the marbling score when using SRU instead of feed-grade urea, but this effect was not supported by differences in the meat chemical composition.…”
Section: Carcass and Meat Quality And Feeding Costsmentioning
confidence: 98%
“…In concordance with our study, Bourg et al [13] did not observe differences in the meat chemical composition when comparing conventional urea with SRU in finishing steers. Cardoso et al [64] reported a reduction in the marbling score when using SRU instead of feed-grade urea, but this effect was not supported by differences in the meat chemical composition.…”
Section: Carcass and Meat Quality And Feeding Costsmentioning
confidence: 98%